Lineamientos generales para impulsar la agricultura de granos y hortalizas del municipio de Yurécuaro, Michoacán como una actividad económicamente sustentable (1990-2010) - Tinajero Alvarado, Juana Yadira (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
In this research an analysis about the actual conditions of the agriculture is presented, particularly the linked to the cultivation of grains and vegetables which is directly related with the consumption and nutrition of the farmer’s families living in the municipality of Yurécuaro. This research work is focused on the principles and postulates of the sustainability. It is performed an analysis about the economic sustainability condition of the agriculture, and from that condition a link is done with the social equity, and also with the environmental viability. Based on such analysis, a set of guidelines are presented which are mainly focused in the betterment of the socio-economic and environmental conditions of the population living in the municipality of Yurécuaro. Yurécuaro is a key municipality, not only by the grains and vegetables cultivation, but also by the numerous day laborers families that every year immigrate to this region to work in the crop fields. Hence the importance to perform a study based on the constructive and criticism analysis focused on the betterment of the socio-economic and environmental conditions from the sustainability perspective. It is important to say that this research work found sense and impulse in the master program Gestión Pública de la Sustentabilidad from the Postgraduate Studies Division of the Economy Faculty “Vasco de Quiroga” at the Michoacan University of Saint Nicholas of Hidalgo.

En la presente investigación se presenta un análisis de las condiciones actuales de la agricultura, en particular la vinculada a granos y hortalizas por ser ésta la que se encuentra vinculada a la alimentación y consumo de las familias de productores en primera instancia, en el municipio de Yurécuaro. Dicho estudio está basado en los principios y postulados de la sustentabilidad. Se realiza un análisis sobre la condición de la sostenibilidad económica de la agricultura, y desde dicha condición se efectúa una vinculación con la equidad social, y su viabilidad medio ambiental. En base a dicho análisis, se presentan una serie de lineamientos las cuales están enfocadas hacia el mejoramiento de las condiciones socio-económicas y ambientales de los habitantes del municipio de Yurécuaro. Yurécuaro es un municipio clave, no sólo por la producción de granos y hortalizas, sino por la gran cantidad de familias jornaleras que cada año inmigran a esta región para emplearse en los campos de cultivo. De ahí la importancia de realizar un estudio basado en un análisis crítico y constructivo enfocado hacia el mejoramiento de las condiciones tanto socio-económicas como ambientales desde el punto de vista de la sustentabilidad. Cabe mencionar que esta investigación encontró sentido e impulso en el Programa de Maestría de Gestión Pública de la Sustentabilidad de la División de Estudios de Posgrado de la Facultad de Economía “Vasco de Quiroga” de la Universidad Michoacana de San Nicolás de Hidalgo.
Facultad de Economía Vasco de Quiroga. Maestría en Gestión Pública de la Sustentabilidad
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2019-0363; Jornaleros; Campo; Calidad de vida; Medio ambiente; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5029